Immunosuppressants in dermatology on vaccine immunogenicity: a prospective cohort study of pemphigus patients in the pandemic - Lu, Kun-Lin; Lee, Hua-En; Chen, Chun-Bing; Hui, Rosaline Chung-Yee; Chang, Ya-Ching; Lu, Chun-Wei; Wang, Chuang-Wei; Chung, Wen-Hung (Frontiers in Immunology, 2024)
IntroductionBoth cellular and humoral responses are important for vaccine protection, but recommendations on immunosuppressants in dermatology are largely based on pre-pandemic experiences. This study aimed to investigate the impacts of immunosuppressants on humoral and cellular immunogenicity to COVID-19 vaccinations in pemphigus patients.MethodsSARS-CoV-2-naïve pemphigus patients and age-, and sex-matched healthy controls were recruited from multiple tertiary medical centers during 2021-2023. Anti-spike protein-related T-cell responses, antibody titers, and high-parameter cell analysis of the peripheral blood were utilized to investigate the inhibitory effects of immunosuppressants, including rituximab and azathioprine.ResultsA total of 32 patients and 120 healthy controls were enrolled. COVID-19 vaccinations spaced at least six months after the last rituximab infusion did not cause a significant difference in anti-viral T-cell or antibody responses between rituximab-naïve and rituximab-treated patients. All pemphigus patients demonstrated improved antibody responses after the third vaccination and none of them suffered from severe COVID-19 illness. Intriguingly, we found that daily dosages of 100 mg or more of azathioprine were linked to significantly decreased anti-viral T-cell responses induced by the vaccination (mean of fold change [SD]; higher azathioprine dosage = 0.70 [0.61] folds vs. lower azathioprine dosage = 2.11 [1.03] folds; p = 0.044).ConclusionExcept for a subset of patients with unrecovered B-cell deficiency, rituximab infusion with proper scheduling of vaccination preserved better anti-viral T-cell responses and did not lead to hindered antibody responses in pemphigus patients. All pemphigus patients benefited from receiving the third booster regardless of B-cell status.